Reading the Simplified Psychrometric Chart for Frost Protection - Ray A. Bucklin; Dorota Z. Haman; Haimanote K. Bayabil; Sandra M. Guzman (EDIS)
Provides growers with an introduction to psychrometrics, which can be used as a tool to time the use of frost protection methods. Includes examples and charts.